Retrograde Recanalization of Occluded Radial Artery: A Single-Centre Experience and Literature Review. (October 2022) - Shi, Ganwei; Li, Feng; Zhang, Liuyan; Gong, Chun; Xue, Sheliang; Song, Yanbin; Cai, Gaojun
Purpose: Radial artery occlusion (RAO) is one of the common complications after coronary intervention via the conventional radial artery approach. The purpose of the study was to explore the safety and feasibility of retrograde recanalization of the occluded radial artery via a distal radial artery (DRA) approach. Methods: Combined with the practice of our centre and a literature review, we summarized the procedure of retrograde recanalization of RAO, success rate, and complications. Results: A total of 14 of 15 patients with 15 pieces of occluded radial arteries were successfully recanalized via the DRA in our centre. In the 15 occluded vessels, 11 vessels (73.3%) had total occlusion and 4 vessels (26.7%) had functional occlusion. Four of 15 occluded vessels were acute occlusions. Two acute RAOs were only treated with aspiration via sheath, 11 RAOs with balloon angioplasty, and 2 RAOs with both, respectively. In 6 patients, cardiac catheterization was carried out via the DRA after recanalizing the RAO. A total of 10 studies reporting the results of recanalization of RAO via the DRA were systematically retrieved in the present study. In 3 case series, the number of cases was more than 5, and the success rate of recanalization was more than 85.7%. Two studies reported complications, including dissection in one case, hematoma in 2 cases, and pain in the forearm during angioplasty. Conclusions: Recanalization of the occluded radial artery via the DRA was safe and effective. When repeat cardiac catheterization was required, recanalization of the RAO and subsequent coronary angiography or intervention through the ipsilateral radial artery approach was feasible.